China's Support for Indonesia's ASEAN Our Eyes Initiative in Countering Cyberterrorism in Southeast Asia - Khoirunnisa, Khoirunnisa; Jubaidi, Didi (The Republic of Indonesia Defense University, 2025)
The ASEAN Our Eyes Initiative (OEI) was established as a regional intelligence-sharing platform in response to the growing threat of cyberterrorism in Southeast Asia. As the initiator, Indonesia has demonstrated regional leadership in promoting collective security based on ASEAN’s core principles of identity, nationalism, and strategic integrity. China’s increasing involvement in OEI-related activities introduces a complex strategic dynamic. On one hand, China’s technological support and intelligence-sharing capabilities have the potential to enhance ASEAN’s cyber defense. On the other hand, dependence on external actors may undermine ASEAN’s strategic autonomy and weaken its leadership in regional security affairs. This study offers a novel contribution by critically examining the ambivalent role of China in the OEI, an aspect that remains underexplored in current defense literature. Using a qualitative approach through a structured literature review, this research analyzes academic publications, official defense policies, and intelligence-related reports to evaluate both the benefits and risks of China’s participation. The findings indicate that while China’s involvement can significantly enhance ASEAN’s operational capacity in addressing cyberterrorism, it also carries the potential to shift the regional balance of power, thereby threatening ASEAN’s identity and independence as a security actor. This leads to clear policy implications in which ASEAN, particularly Indonesia, must establish transparent and rules-based cooperation frameworks to define the boundaries of external engagement. Strengthening intra-ASEAN collaboration and investing in domestic cyber defense capabilities are essential to safeguarding the sustainability of OEI. By maintaining a careful balance between external support and regional sovereignty, OEI can continue to serve as a credible, ASEAN-driven security mechanism. This study recommends enhancing joint oversight mechanisms, legal safeguards, and internal resilience to ensure that the initiative remains rooted in the region’s foundational values of unity, autonomy, and collective integrity.